Membangun Personal Branding 'Positif Energy' Melalui Media Sosial Shasa Zhania - Khotimah, Aliya; Rusdi, Farid (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
TikTok's popularity rising. Number of women 16-24 years old considering it their